Managing the herdbook of an endangered Portuguese swine population: the Malhado de Alcobaça pig - Vicente, António (2020)
Malhado de Alcobaça breed is the 3rd Portuguese native swine breed and represents a population from the centre west of Portugal and was officially recognised in 2003. The herdbook has information of more than 11,000 animals (1985-2020) and the last animals have more than 10 known generations on their pedigree. It´s a very endangered breed with only 211 breeding sows, 12 boars and 9 active breeders. Since 2014 all candidates for breeding must be submitted to a grading process by analysing their morphology under 5 marks and, at the same time, placing an ear tag ID, collecting, simultaneously, tissue for DNA analysis, for parentage testing and genetic characterisation. All data from the gradings was analysed to obtain the descriptive statistics and the linear and quadratic effect of age at grading, besides considering the effects of breeder, gender and year. Since 2014, 448 pigs where graded (415 sows and 33 boars) with average age of 15.87±8.88 months (15.96±8.99♀; 14.61±7.35♂). Only 7 different breeders produced breeding sows and boars, and 4 of them are responsible for 83% of the breeding stock in use. For the grading grid (scale with maximum of 10 pts.) the average scores for morphology were 8.54±0.72 pts for type and development; 8.35±0.68 pts for back, loin and croup; 8.24±0.64 pts for shoulders, chest, belly and flanks; 7.99±0.81 pts for legs, stances and gaits; and 8.43±0.66 pts for sexual characteristics, genitals and nipples, obtaining and overall sum of 82.58±4.45 pts. Globally boars obtain more 1.5 points than sows and the score for legs was the lowest with higher coefficient of variation. Breeder and year of grading were significant (P<0.05) for all morphological traits analysed and gender was only significant (P<0.001) for back, loin and croup. Age at grading had a significant linear effect (P<0.05) in Overall sum and for some partial morphological scores